Assessing the digital divide between the rural and urban areas of Sarawak using the system dynamics model / Wong Muk Ngiik... [et al.] - Ngiik, Wong Muk; Hamali, Jamil; Yin, Yap; Hok, Chong Vui; Singh, Kuldip; Johneny, Stalin; Jingut, Robert (Universiti Teknologi Mara Cawangan Sarawak, 2009)
The rapid pace of development and adoption of ICT brings economic growth and development to many countries in the world, but it also has led to an undesirable phenomenon known as the 'digital divide' among them. In this study, "Digital divide" is the disparity in terms of access to ICT infrastructures and the effective adoption of ICT to enhance the quality of life. The purpose of this study is to identify the main determinants of digital divide in Sarawak and to develop the Digital Divide Index (DDex) to assess the extent of digital divide between the urban and rural areas in Sarawak using the System Dynamic technique (SD technique). The information used in this study are obtained from both existing government publications and a survey that covers a total of 1,034 respondents in selected localities in Sarawak. The analysis instrument is the System Dynamic model which incorporates three domains and twelve indicators. The respective domains and indicators are: Infrastructure (Supply of Electricity, Availability of Internet Services, Proximity to Internet Service Centres); Socio-Economic variables (Highest Educational Attainments, Occupational Hierarchy, Income, Skills, and Language Proficiency); and Social capital (Quality of Life, Personal Weil-Being, Desire to know about other culture and Perception of neighbourhood). This study reveals that there is significant digital divide between the rural and urban population of Sarawak. The main determinant of digital divide is found to be the socio-economic variable in particular the low parity share of the rural population in educational attainment resulting in the unequal diffusion of the benefits of economic development to the people in the rural area of Sarawak This study concludes that an effective affirmative action plan together with an effective delivery process is needed to propel the rural population to the knowledgebase economy where the skill level of the labour force need to be recalibrated from ICT illiteracy to functional literacy in ICT and finally to competency in ICT. In the absence of such a plan, the rural population may become economically excluded and marginalized. A number of recommendations are made to bridge the digital divide gap in Sarawak.